OPPORTUNITIES FOR THE DEVELOPMENT OF THE INTERNATIONAL PILGRIMAGE TOURISM IN UZBEKISTAN - Yuldasheva Dilnoza Bekmurodovna; Egamkulov Davlatbek Bakhodirovich (Galaxy International Interdisciplinary Research Journal, 2023)
Uzbekistan, with its long history and ancient culture, has a huge untapped potential for tourism development in international and regional markets. Recreational resources and the tourist potential of historical and cultural heritage will allow Uzbekistan to harmoniously enter the international pilgrimage tourism market and accelerate the development of tourism in the country. This will ensure sustainable growth of employment and income, stimulate the development of tourism-related industries and increase the inflow of investment into the national economy.